Optimalisasi Pengecekan dan Perbaikan dengan Penentuan Ukuran Utama Penutup Bawah pada Tangki Timbun di PT. KPBN Belawan - Silalahi, Krisanto; Tarigan, Nurlianna (CV. IRA PUBLISHING, 2024)
PT. KPBN Belawan is a company branch entrusted as an agent for buying and selling CPO (Crude Palm Oil). PT. KPBN Belawan operates a tank storage unit that temporarily stores CPO before selling it to customers. Regular inspections are necessary for the storage tanks, such as checking the thickness of the tank plates and ensuring the strength of the locking mechanisms on the shell central hole to prevent leaks during filling. This research aims to calculate the dimensions of the bottom cover of the storage tank (central hole), which serves as a seal for the CPO in a storage tank with a capacity of 5,000 liters. The calculated dimensions for the shell central hole are as follows: the nominal diameter of the shell maintenance hole bolts is 17.5 mm, the flange width is 40.25 mm, the outer diameter of the flange shell maintenance hole is 913.6 mm, the bolt circle diameter of the flange shell central hole is 887 mm, the inner diameter of the flange shell central hole is 869.5 mm, the number of bolts is 24, the flange thickness is 18 mm, and the bolt spacing of the flange shell mainhole is 115.77 mm.